2020
DOI: 10.1186/s12891-020-03302-5
|View full text |Cite
|
Sign up to set email alerts
|

Residual leg numbness after endoscopic discectomy treatment of lumbar disc herniation

Abstract: Background Transforaminal endoscopic discectomy was popular in the treatment of lumbar disc herniation. Previous study focuses on the leg pain of disc herniation, and little study concern the residual leg numbness after surgery. The purposes of this study were to evaluate the clinical outcomes of transforaminal endoscopic discectomy in the treatment of lumbar disc herniation with leg pain and numbness. Methods Patients with one level lumbar disc he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Our investigation was strictly focused on correlation between LDH and motor disturbances; numbness and sensitive disturbances, in fact, are frequently reported at the beginning of clinical presentation and strictly related to onset of pain, thus being difficult to prevent. 24 Moreover, sensitive impairment shows a weaker correlation with ODI score when compared with pain score and motor deficit, thus suggesting a lesser influence on social dysfunction. 25 Another possible limitation may be the fact that MRI images have been classified by only 1 reader; thus, the study considered neither intra-rater nor interrater variability.…”
Section: Discussionmentioning
confidence: 99%
“…Our investigation was strictly focused on correlation between LDH and motor disturbances; numbness and sensitive disturbances, in fact, are frequently reported at the beginning of clinical presentation and strictly related to onset of pain, thus being difficult to prevent. 24 Moreover, sensitive impairment shows a weaker correlation with ODI score when compared with pain score and motor deficit, thus suggesting a lesser influence on social dysfunction. 25 Another possible limitation may be the fact that MRI images have been classified by only 1 reader; thus, the study considered neither intra-rater nor interrater variability.…”
Section: Discussionmentioning
confidence: 99%
“…In ammatory responses are known as a major component of secondary injury of initial ischemic insult and play an important role in modulating the pathogenesis of leg numbness [26,25]. The leg numbness symptoms were last longer in central disc herniation patients than in paracentral and foraminal disc herniation patients after surgery, which means the in ammatory response from herniated herniate disc fragments compression nerve may be an important factor in affection on it.…”
Section: Discussionmentioning
confidence: 99%
“…Although patients with leg pain and leg numbness pre-operation complain of leg numbness during or just after walking or standing not diminished after surgery, the leg numbness dismissed were 6 months post-operation in lateral herniation patients and 12 months post-operation in central herniation patients. Then, percutaneous one portal transforaminal endoscopic lumbar discectomy is the preferred minimally invasive approach in two-level disc herniation case due to less trauma, less blood lost, and short operation time, and faster recover [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toyoda et al performed a cluster analysis on patients, and found that despite an improvement after spinal endoscopic surgery, cluster 4 patients retained severe leg numbness, postoperatively [ 8 ]. Yan et al showed that patients with central disc herniation displayed a longer duration of leg numbness after spinal endoscopic surgery than patients with paracentral disc herniation [ 9 ]. Ogura et al showed that 60% of patients retained leg numbness after spinal endoscopic surgery [ 10 ].…”
Section: Introductionmentioning
confidence: 99%